Sistemas e ciclos de monitoramento e avaliaç\~ao: Recomendaç\~oes da análise ex ante de políticas públicas e de programas governamentais - Antônio Lassance (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The ex ante analysis aims, among other aspects, to formulate public policies and design government programs that are born ready to be monitored and evaluated. Evidence-based policies and programs may be improved only if each step taken by public action leaves some traces for the monitoring of inputs, processes, and outputs. In the long run, the monitoring system must leave clues that can be used to identify the results and impacts of the policy or program that have been sedimented along the way. This Discussion Paper complements the previous Ex Ante Analysis of Public Policies: theoretical-conceptual foundations and methodological guidelines for practical purposes (Discussion Paper, n. 2817). While that previous study details and guides the use of theoretical references and serves as a methodological guide for the ex ante analysis, this work is devoted to exploring how to design and implement monitoring and evaluation systems and cycles. This paper encourages the emergence of a community of experts on guidance and facilitating activities aimed at ex ante analysis. This qualification is essential for crafting policies and programs to demonstrate their raison d'être to the public and their biggest and best benefits to society.
10419/284914
Keywords: D04; H11; H4; 330; Ex ante analysis of public policies; formulation; implementation; monitoring; evaluation; microeconomic public policy